2012
DOI: 10.1038/jhg.2011.139
|View full text |Cite|
|
Sign up to set email alerts
|

Spectra of BRCA1 and BRCA2 mutations in Korean patients with breast cancer: the importance of whole-gene sequencing

Abstract: The frequencies and spectra of germline mutations in the BRCA1 and BRCA2 genes vary among populations. In the present study, the mutation spectra of the BRCA1/BRCA2 genes in Korean breast cancer patients were investigated using whole-gene sequencing method. A total of 134 unrelated Korean breast cancer patients who were identified as being at high risk of carrying BRCA1/BRCA2 mutations were included. PCR amplification and direct sequencing were performed covering all exons and flanking intronic sequences of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The fact that it was recurrently found in patients with HBOC or ovarian cancer but not in general population (not recorded in the dbSNP and the 1,000 Genome Project databases) strongly supported its pathogenicity. All previously reported cases affected by this mutation were Asian patients from China and South Korea . This mutation seemed to be substantially enriched in Chinese populations and was reported mostly from HBOC breast cancer patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The fact that it was recurrently found in patients with HBOC or ovarian cancer but not in general population (not recorded in the dbSNP and the 1,000 Genome Project databases) strongly supported its pathogenicity. All previously reported cases affected by this mutation were Asian patients from China and South Korea . This mutation seemed to be substantially enriched in Chinese populations and was reported mostly from HBOC breast cancer patients.…”
Section: Discussionmentioning
confidence: 91%
“…All previously reported cases affected by this mutation were Asian patients from China 20 and South Korea. 36,37 This mutation seemed to be substantially enriched in Chinese populations and was reported mostly from HBOC breast cancer patients. Based on data from cohorts of >200 patients, the incidence was reported to be 0.1% (1/505), 0.3% (2/625) and 0.4% (1/219).…”
Section: Discussionmentioning
confidence: 99%
“…ClinVar and SCRP also list three submissions with a VUS interpretation. Interestingly, other reports of this variant are restricted to studies using Korean cohorts, all of which classify the variant as VUS [ 12 , 22 - 24 ]. In our study, this variant was found in 11 cases and was the second most common mutation after BRCA1 c.3627dupA (12 cases).…”
Section: Discussionmentioning
confidence: 99%
“…This common geographical distribution of the BRCA2 frameshift to close maghrebian countries (Algeria, Morocco and Tunisia) could be explained by geographical proximity and migration flow history. Much further from North-African area, the c.1310_1313delAAGA mutation, was carried by one Korean subject among the 31 patients with BRCA mutations of the 134 unrelated Korean hereditary breast cancer patients tested [21]. The c.1310_1313delAAGA presumably occurred several times at unstable mutational hot spots parts of the gene in different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%